2007
DOI: 10.17221/2100-swr
|View full text |Cite
|
Sign up to set email alerts
|

Revised soil erodibility K-factor for soils in the Czech Republic

Abstract: Abstract:In the territory of the Czech Republic there are more than 50% of agricultural soils exposed to water erosion; it is a very urgent problem both at present and for the future. It must be solved now when there is still something to be protected. It is rather complicated to describe the soil properties in terms of soil susceptibility to water erosion because it is a complex relation in which many factors participate. For the complex evaluation of all main factors participating in erosion origination it i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 0 publications
1
14
0
Order By: Relevance
“…1) were found in the southeast part of the Czech Republic, and there is also a small area in the north-western part of the Czech Republic. These results correspond very well with the fact that wind erosion has been often observed and measured at these localities (Mužíková et al, 2010;Švehlík, 1985;Vopravil et al, 2007). In specific areas, the erosion loss of 2 mm aggregates could be expected.…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…1) were found in the southeast part of the Czech Republic, and there is also a small area in the north-western part of the Czech Republic. These results correspond very well with the fact that wind erosion has been often observed and measured at these localities (Mužíková et al, 2010;Švehlík, 1985;Vopravil et al, 2007). In specific areas, the erosion loss of 2 mm aggregates could be expected.…”
Section: Resultssupporting
confidence: 87%
“…Due to alternating freezing and thawing of the soil surface, there occurs a significant collapse of soil structure on Haplic Chernozem (Siltic), Haplic Chernozem (Clayic), Haplic Cambisol (Clayic) (IUSS, 2006;Vopravil et al, 2007) primarily in the winter period, and so soils generally considered as invulnerable to wind erosion (Chepil, 1953) due to grain size, are highly threatened by wind erosion. These represent an anomaly, because heavy-textured soils are generally not susceptible to wind erosion.…”
Section: Introductionmentioning
confidence: 99%
“…The K factor of Cambisols of the field varies from 0.16 to 0.49 t/N (0.26 t/N on average). It was derived from soil bonity vector maps (BPEJ) on a 1 : 5000 scale, using the official relation of Vopravil et al (2007). Apart from the land-use pattern, all parameters were kept constant for different time periods in order to address directly the influence of landscape variability.…”
Section: Methodsmentioning
confidence: 99%
“…The results indicated that soils of watershed are dominated by two types as; Eutric Cambisols and Chromic Cambisols. According to Vopravil et al (2007), soil erodibility value adopted to Eutric Cambisol is 0.32 Mg h MJ −1 mm −1 and average value of 0.33 Mg h MJ −1 mm −1 of Cambisols is adopted for Chromic Cambislos. The soil distribution and soil erodibility map is presented in Fig.…”
Section: Soil Erodibility Factor (K)mentioning
confidence: 99%